2003
DOI: 10.1097/00007691-200302000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Failure of Nelfinavir-Containing Triple Therapy Can Largely Be Explained by Low Nelfinavir Plasma Concentrations

Abstract: The relationship between plasma concentrations of nelfinavir and virologic treatment failure was investigated to determine the minimum effective concentration of nelfinavir. Plasma samples were prospectively collected from treatment-naive patients who began taking nelfinavir, 1,250 mg BID + two nucleoside reverse transcription inhibitors (NRTIs). Nelfinavir concentration ratios were calculated by dividing each individual nelfinavir level by the time-adjusted population value. Virologic failure was defined as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 22 publications
2
48
1
Order By: Relevance
“…5 Morning trough concentrations of nelfinavir less than 1.4mg/l (also expressed as a concentration ratio of less than 0.9) were found to increase significantly the risk of virologic failure. 6 A prospective study of nelfinavir therapeutic drug monitoring in 92 adult patients demonstrated an improved virologic response after 1 year of follow-up with 81% of subjects who received therapeutic drug monitoring having HIV RNA < 500 copies/ml compared with 59% of those who received standard dose therapy.7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Morning trough concentrations of nelfinavir less than 1.4mg/l (also expressed as a concentration ratio of less than 0.9) were found to increase significantly the risk of virologic failure. 6 A prospective study of nelfinavir therapeutic drug monitoring in 92 adult patients demonstrated an improved virologic response after 1 year of follow-up with 81% of subjects who received therapeutic drug monitoring having HIV RNA < 500 copies/ml compared with 59% of those who received standard dose therapy.7…”
Section: Discussionmentioning
confidence: 99%
“…AUCs for efavirenz and nelfinavir were determined at weeks 2 and 6 in all children; those children who had not achieved efavirenz or nelfinavir concentrations within the target range had additional pharmacokinetic evaluations at week 10. Blood samples were obtained pre-dose and 2, 5,6,8,12, and 24 h post-dose. Plasma concentrations were determined within 2 weeks at a PACTG Pharmacology Laboratory by high-performance liquid chromatography.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…The long-term success of ARV treatment depends upon maintaining inhibitory concentrations of active drug at the site of HIV replication sufficient to suppress viral replication. Reduced serum levels of ARV drugs correlate with treatment failure and the development of ARV drug resistance [39][40][41][42]. High serum levels of ARV drugs have been shown to correspond with an increased incidence of [26][27][28] Some patients were issued with warnings for more than one adverse effect or interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum (C max ) and trough (C res ) plasma concentrations were then calculated according to a classical steady-state formulae for repeated oral dose: At steady state, area under the plasma curve up to 8h after intake (AUC 0-8h ), was estimated by the Dose/CL ratio. The observed/predicted concentrations ratio (CR) was estimated by the ratio between the observed concentration and the predicted concentration at the same time using the mean population parameters estimated during the population analysis (10 into account because they are the most frequent and specific SAR related to indinavir use (18)(19)(20)(21)(22)(23). Then, all SAR (including nephrolithiasis) and SAR excluding nephrolithiasis were studied in two secondary analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies in HIV-infected patients have previously focused on a relationship between concentration and effect, in terms of virological response (8)(9)(10)(11), whereas toxicity was a secondary outcome. When adverse events have become a major problem in treated HIV-infected patients, data found in the literature show insufficient evidence to recommend a general therapeutic range, probably because only few databases have both appropriate pharmacokinetics and toxicity data available, like in the ANRS CO8 APROCO-COPILOTE cohort.…”
Section: Introductionmentioning
confidence: 99%